2016
DOI: 10.3389/fpls.2016.00250
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Morphology, Photosynthetic Performance, Chlorophyll Fluorescence, Stomatal Development of Lettuce (Lactuca sativa L.) Exposed to Different Ratios of Red Light to Blue Light

Abstract: Red and blue light are both vital factors for plant growth and development. We examined how different ratios of red light to blue light (R/B) provided by lightemitting diodes affected photosynthetic performance by investigating parameters related to photosynthesis, including leaf morphology, photosynthetic rate, chlorophyll fluorescence, stomatal development, light response curve, and nitrogen content. In this study, lettuce plants (Lactuca sativa L.) were exposed to 200 µmol·m −2 ·s −1 irradiance for a 16 h·d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

42
273
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(324 citation statements)
references
References 53 publications
(84 reference statements)
42
273
3
6
Order By: Relevance
“…Stomatal aperture is also larger under B LEDs than R and W LEDs [19,71]. In general, elongation of the guard cell is subject to widening of the stomatal opening [72], and loss of water from the guard cell drives stomatal closure [73]. We found that the increase in guard cell length, width, and area in the leaves treated with B LEDs relative to the other LEDs may be associated with stomatal conductance ( Figure 5(A1-A3,b1-b3); Figure S1).…”
Section: Discussionmentioning
confidence: 94%
“…Stomatal aperture is also larger under B LEDs than R and W LEDs [19,71]. In general, elongation of the guard cell is subject to widening of the stomatal opening [72], and loss of water from the guard cell drives stomatal closure [73]. We found that the increase in guard cell length, width, and area in the leaves treated with B LEDs relative to the other LEDs may be associated with stomatal conductance ( Figure 5(A1-A3,b1-b3); Figure S1).…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that red light plays important role in shoot elongation and plant anatomy via phytochrome (Schuerger et al, 1997) while blue light is important for Chl biosynthesis (Tripathy and Brown, 1995; Matsuda et al, 2008; Hogewoning et al, 2010; Terfa et al, 2013; Hernández and Kubota, 2016), stomatal development and opening (Hogewoning et al, 2010; Wang et al, 2016). However, very little published information is available on the use of different red- and blue-LEDs combinations to study plants at different growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…In the study with lettuce grown under mixture of red and blue light or blue light treatments had a higher Chl a / b compared with red light treatment (Wang et al, 2016). Blue light can be absorbed either by Chl or by Car for the formation of “sun-type” chloroplasts (López-Juez and Hughes, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light quality strongly mediates the operation of the leaf photosynthetic apparatus (Hogewoning et al , Bugbee , Song et al ). Blue (400–500 nm) and red (600–700 nm) light play pivotal roles in determining leaf photosynthesis, as red light has the highest quantum yield (McCree ), and blue light is involved in stomatal opening and leaf photosynthetic functioning (Wang et al , ). Earlier studies reported that plants grown under monochromatic red light suffer a spectral ‘deficiency’ syndrome, which is characterized by abnormal photosynthetic functioning (Trouwborst et al ).…”
Section: Introductionmentioning
confidence: 99%